Q. Draw the expression tree of the infix expression written below and then convert it intoPrefix and Postfix expressions.
((a + b) + c * (d + e) + f )* (g + h )
Ans:
The expression given is:
The postfix expression obtained is:
((a+b)+c*(d+e)+f)*(g+h)
= ((ab+)+c*(de+)+f)*(gh+)
= ((ab+)+(cde+*)+f)*(gh+)
= ((ab+cde+*+)+f)*(gh+)
= (ab+cde+*+f+)*(gh+)
=(ab+cde+*+f+gh+*)
The prefix expression obtained is:
= ((+ab)+c*(+de)+f)*(+gh)
= ((+ab)+(*c+de)+f)*(+gh)
= ((++ab*c+de)+f)*(+gh)
= (+++ab*c+def)*(+gh)
= (*+++ab*c+def+gh)